1980
DOI: 10.1111/j.1467-6494.1980.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social cues on the eating behavior of obese and normal subjects1

Abstract: Schachter's externality hypothesis suggests that overweight individuals are more likely to be induced to eat by salient external cues than normal weight individuals. While a range of studies have demonstrated the plausibility of this hypothesis in the case of sensory stimuli (e.g., taste cues), there is little evidence that the hypothesis applies to social stimuli. The current study examines this latter proposition by exposing male and female, overweight and normal weight subjects to a same-sex or opposite-sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 17 publications
7
73
1
1
Order By: Relevance
“…These and other muscle groups associated with bolus acceptance and preparation also must be properly choreographed with the rhythm and pace of upper limb movements while eating. Societal factors, anxiety, food palatability, and the degree of hunger or satiety modify eating and swallowing rate in normal subjects [14][15][16][17][18]. Psychosocial factors influence the presence and timing of aspiration of elderly nursing home patients [19].…”
Section: Pre-oral (Anticipatory) Stage: Interstage Relationshipsmentioning
confidence: 99%
“…These and other muscle groups associated with bolus acceptance and preparation also must be properly choreographed with the rhythm and pace of upper limb movements while eating. Societal factors, anxiety, food palatability, and the degree of hunger or satiety modify eating and swallowing rate in normal subjects [14][15][16][17][18]. Psychosocial factors influence the presence and timing of aspiration of elderly nursing home patients [19].…”
Section: Pre-oral (Anticipatory) Stage: Interstage Relationshipsmentioning
confidence: 99%
“…Weight status has been suggested as a potential characteristic that might have an effect on whether or not we are influenced by the eating behaviour of others, but previous studies have produced mixed findings (Conger, Conger, Costanzo, Wright, & Matter, 1980;Hermans, Larsen, Herman, & Engels, 2010;Johnston, 2002;McFerran, Dahl, Fitzsimons, & Morales, 2010). Most recently, Hermans et al (2010) found that healthy weight females modelled the intake of a live eating companion only when that companion appeared to be a similar weight and not when the eating companion appeared slimmer.…”
Section: Introductionmentioning
confidence: 94%
“…In such studies, the amount of food the model consumes is always predetermined by the experiment, and respondents display suppressed food intake when accompanied by somebody eating very little but elevated food intake when in the company of somebody eating a lot of the same food. Interaction effects have appeared for participants' and confederates' gender and weight, dieting habits, and hunger states (Conger, Conger, Costanzo, Wright, & Matter, 1980;Goldman, Herman, & Polivy, 1991;Rosenthal & McSweeney, 1979). Herman, Polivy, and Roth (2003) also refer to the process of mimicking food intake as a "matching norm" that reveals the appropriate amount of food in social consumption situations.…”
Section: Social Influence On Food Consumptionmentioning
confidence: 99%